Case studies of tutors' responses to student writing and the way in which students interpret these - Paxton, Moragh Isobel Jane (Rhodes University, Faculty of Education, Department of Education, 1994)
This thesis examines tutor feedback on student essays to ascertain the extent to which these responses assist in teaching the academic and specific disciplinary conventions and to determine what is effective feedback and what is not. The investigation constituted an evaluation of a small sample of essays and the framework for this evaluation was developed from a study of current theories of literacy and language teaching. It was further informed by data gathered from interviews with students and tutors and questionnaires completed by them. This was done in order to establish how students interpret and react to feedback and to demonstrate the level of understanding between tutors and students in this mode of communication. The conclusion was that tutor feedback can provide a valuable method for teaching the discourse of the discipline. However, results of the study revealed that communication often breaks down because tutors and students do not share a common language for talking about academic discourse and because students may not have understood the requirements of the task. In addition, the study found that responses to a small group of essays in the lowest mark category and written by second language students, were very inadequate. As the researcher, I concluded that graduate tutors were not well equipped for the task of dealing with these weaker essays. I have made suggestions for future research in this area and I believe that the data from this case study will provide valuable ideas for training tutors for responding to student essays.
Keywords: Written communication -- Study and teaching -- South Africa; Written communication -- South Africa -- Case studies; Grading and marking (Students) -- Case studies